WAYS TO IMPROVE THE MANAGEMENT OF SMALL AND MEDIUM BUSINESSES IN THE DIGITAL ECONOMY - Tursunov, Imomnazar; Nasrullayev, Feruz; Bozorov, Samar (Innovatsion texnologiyalar, 2024)
The article describes the role, essence and significance of the digital and innovative economy in increasing the competitiveness of private entrepreneurship, small and medium-sized businesses. Also, proposals were put forward for their development in connection with the integration of science and higher education and internal and external factors of technological development